2003
DOI: 10.1152/ajplung.00023.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced calcium signaling to bradykinin in airway smooth muscle from hyperresponsive inbred rats

Abstract: Inbred Fischer 344 rats display airway hyperresponsiveness (AHR) in vivo compared with the normoresponsive Lewis strain. Fischer AHR has been linked with increased airway smooth muscle (ASM) contraction ex vivo and enhanced ASM cell intracellular Ca(2+) mobilization in response to serotonin compared with Lewis. To determine the generality of this association, we tested whether bradykinin (BK) also stimulates greater contraction of Fischer airways and greater Ca(2+) mobilization in Fischer ASM cells. Explants o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…These observations are consistent with the findings reported by Tao and colleagues (27,28). Nevertheless, the mechanism for the modulation of calcium responses of BSMCs to inflammatory cytokines is largely unexplored.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations are consistent with the findings reported by Tao and colleagues (27,28). Nevertheless, the mechanism for the modulation of calcium responses of BSMCs to inflammatory cytokines is largely unexplored.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicate that cADPR does not contribute to airway inflammation-induced dissociation of FKBP12.6 from the RyR2. Ca 21 mobilization from SR in BSMCs in response to contractile agonists such as bradykinin or acetylcholine is an important component of smooth muscle contraction (12,28,30). When dissociated from FKBP12.6, the RyR2 calcium channel on the SR membrane has more opening probability and becomes sensitized to intracellular activator signals.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the present study shows that both LY294002 and Gö6983 exhibit Ca 2ϩ antagonistic properties in the concentration range usually applied to selectively block PI3-K (Quignard et al, 2001;Northcott et al, 2002;Wang et al, 2002;Callaghan et al, 2004;McDowell et al, 2004) and PKC (Tao et al, 2003), respectively. Therefore, evidence of a functional coupling of the PI3-K signaling pathway to L-type Ca 2ϩ -channel activity is hampered by the inhibitory effects of the compounds LY294002 and Gö6983 on L-type Ca 2ϩ channels.…”
Section: Resultsmentioning
confidence: 57%
“…The signaling pathway underlying BK-induced currents in ASM cells is still uncertain. Several studies have shown that BK is a Gq/G 11 -coupled receptor agonist with the potential to couple to phosphatidylinositidespecific phospholipase C (PI-PLC) (45), phosphatidylcholine phospholipase C (PC-PLC) (37), or phospholipase D (36). Stimulation of PI-PLC will promote the production of the second messenger, IP 3 , which releases Ca 2ϩ from intracellular stores to the cytoplasm, and 1,2-diacylglycerol, which activates PKC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ion channel activity is altered in ASM cells from rats with a hyperresponsive phenotype (45), in atrial myocytes grown in an altered extracellular matrix environment (49), in smooth muscle cells exposed to proinflammatory mediators (19), and following exposure to environmental toxins (52). K ϩ channels other than BKCa may thus assume greater importance in ASM cell function in the asthmatic airway, where the matrix environment is altered and inflammatory mediators abound.…”
mentioning
confidence: 99%